PERENCANAAN DAKWAH INKLUSIF: REVITALISASI PENDEKATAN TOLERANSI DALAM MASYARAKAT MULTIKULTURAL - Sitti Hamsiyah; Mahmuddin Mahmuddin (J-MD Jurnal Manajemen Dakwah, 2025)
An inclusive, tolerant, and contextual da'wah approach is a compatible strategy to deal with the phenomenon of multicultural society. The sociocultural complexity and diversity of society become the standard of adjustment in da'wah. This study was born to respond to various contemporary da'wah challenges that require a planning strategy based on the principle of inclusiveness. Inclusivity efforts are built on the values of transparency, empathy, and interfaith communication. This study is not only important for the dissemination of religious information, but also for creating social cohesion and as a form of attention in dealing with contemporary conflicts, especially amidst the rise of religious polarization and indications of intolerance. This study utilizes a descriptive qualitative approach by analyzing contemporary da'wah narratives that illustrate inclusive characters. Data collection is done through literature study and observation of da'wah practices by progressive da'i in previous related studies. The results of this study show that inclusive da'wah planning not only requires the maturity of content that is appropriate to the situation, but also responsive to the audience's background and mastering relevant media. Elements of inclusiveness appear in da'wah that prioritizes the use of egalitarian, non-discriminatory, and interactive language. Thus, inclusive da'wah can be an effective strategy in cooperating with groups that have been marginalized, such as minority groups, disabled groups, and lower social strata. Therefore, the principle of inclusiveness in da'wah planning is an important aspect that needs to be applied to realize the mission of Islamic da'wah that is rahmatan lil 'alamin and relevant to the current social conditions of Indonesian society.